2003
DOI: 10.1093/nar/gkg412
|View full text |Cite
|
Sign up to set email alerts
|

The acidic C-terminal domain and A-box of HMGB-1 regulates p53-mediated transcription

Abstract: p53 function is modulated by several covalent and non-covalent modifiers. The architectural DNA- binding protein, High Mobility Group protein B-1 is a unique activator of p53. HMGB-1 protein is structured into two HMG-box domains, namely A-box and B-box, connected to a long highly acidic C-terminal domain. Here we report that both the C-terminal domain and A-box of HMGB-1 are critical for stimulation of p53-mediated DNA binding to its cognate site. Though deletion of these domains showed minimal effect in acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…With rapid advances in cancer researching in the past decade, it is well accepted that HMGB1 is associated with each of the six hallmarks (Tang et al, 2010). Despite its critical roles in nucleus, such as DNA repair, interaction with transcriptional factors like p53, p73 and Rb protein, the functions of extracellular HMGB1 receive a great deal of attention recently (Stros et al, 2002;Banerjee et al, 2003;Krynetski et al, 2003;Jiao et al, 2007). It is noteworthy that HMGB1protein released from cancer cells is a double-edged sword: it promotes tumor neoangiogenesis; it triggers protective anti-neoplastic T-cell responses (Campana et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…With rapid advances in cancer researching in the past decade, it is well accepted that HMGB1 is associated with each of the six hallmarks (Tang et al, 2010). Despite its critical roles in nucleus, such as DNA repair, interaction with transcriptional factors like p53, p73 and Rb protein, the functions of extracellular HMGB1 receive a great deal of attention recently (Stros et al, 2002;Banerjee et al, 2003;Krynetski et al, 2003;Jiao et al, 2007). It is noteworthy that HMGB1protein released from cancer cells is a double-edged sword: it promotes tumor neoangiogenesis; it triggers protective anti-neoplastic T-cell responses (Campana et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 was initially described as a nuclear nonhistone DNA-binding protein that functions as a structural cofactor critical for proper transcriptional regulation (6). It also facilitates numerous nuclear events, including replication, recombination, and DNA transposition (7). Recently, it has been reported that HMGB1 is secreted into the extracellular milieu by activated macrophages, and identified as a late mediator of lethal systemic inflammation in sepsis (8).…”
mentioning
confidence: 99%
“…Inside the cell, HMGB1 binds to DNA and promotes transcription as well as other functions (1,2). Outside the cell, HMGB1 can serve as a cytokine to promote inflammation and induce an array of proinflammatory responses including the expression of TNF-␣, IL-1, and NO, as well as induce the maturation of dendritic cells (3).…”
mentioning
confidence: 99%